Min-Max Decoding-Error Probability-Based Resource Allocation for a URLLC System - Nasir, Ali A. (IEEE communications letters, 2020)
This letter considers an industrial automation scenario where a central controller communicates with multiple machines by transmitting data in short blocklengths. This communication is subject to reliability and latency constraints, which can be referred to as ultra-reliable and low-latency communication (URLLC). With the objective of minimizing the worst-case decoding-error probability for all the machines (min-max decoding-error probability), we consider joint power allocation and transmission blocklength optimization under the subject of transmit power and latency constraints. To solve this challenging problem, we propose a novel path-following algorithm. Simulation results clearly demonstrate the merits of the proposed algorithm.